Characteristics and Deviations of Legal Interpretation: An Epistemological Study of Legal Characteristics in the Interpretation of the Qur'an - Abdullah, Aden Azis; Hamzah, Fahmi (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine in depth the concept, its history of emergence, characteristics, and methodological deviations in tafsir hukmi, one of the styles of Qur'anic interpretation that focuses on the interpretation of legal verses (ahkam shar'iyyah). This study is motivated by the importance of understanding how tafsir hukmi lays the foundation for Islamic law derived from revelation and addresses society's needs. This study uses a qualitative approach with a descriptive-analytical method, namely examining classical and modern tafsir texts oriented towards Islamic law, such as the works of al-Jassas, Ibn al-'Arabi, and al-Qurtubi, as well as contemporary research on the methodology of legal interpretation. Data were obtained through library research on primary and secondary sources, then analyzed using interpretive techniques to identify the characteristics and methodological patterns used in tafsir hukmi. The results of the study indicate that tafsir hukmi emerged during the golden age of Islam (2nd–6th century AH), alongside the development of fiqh and usul fiqh, and served as a bridge between revealed texts and Islamic legal practice. However, several deviations were found, including the subjectivity of schools of thought, the reduction of the spiritual meaning of the verses, the dominance of ra'yu, and the lack of a contextual approach. In conclusion, tafsir hukmi plays a strategic role in integrating revelation and social reality, but must be continuously developed within a maqasid sharia framework to remain relevant to the challenges of contemporary Islamic law.